Unemployment insurance and opioid prescriptions during the great recession. - Guo, Xiaohui; Peng, Lizhong (Southern Economic Journal, 2024)
This is the first U.S. study on the causal relationship between unemployment insurance (UI) expansions during the Great Recession and the use of prescribed opioids. Using annual county‐level prescription data from 2006 to 2013 and plausibly exogenous variation in state and federal policies, we estimate that a one standard deviation increase in UI generosity ($10,800) reduces per‐capita prescription opioid use by 1.9%. We supplement our main analysis with a border discontinuity design and find a similar effect. We also find no evidence of pre‐trends in the outcome. Finally, additional analyses suggest that increased health care utilization after exposure to higher UI generosity could be a plausible explanation for the declines in opioid prescriptions.